Roles of the TRAF6 and Pellino E3 ligases in MyD88 and RANKL signaling - Strickson, Sam; Emmerich, Christoph H; Goh, Eddy T H; Zhang, Jiazhen; Kelsall, Ian R; Macartney, Thomas; Hastie, C James; Knebel, Axel; Peggie, Mark; Marchesi, Francesco; Arthur, J Simon C; Cohen, Philip (Proceedings of the National Academy of Sciences - PNAS, 2017)
It is widely accepted that the essential role of TRAF6 in vivo is to generate the Lys63-linked ubiquitin (K63-Ub) chains needed to activate the "master" protein kinase TAK1. Here, we report that TRAF6 E3 ligase activity contributes to but is not essential for the IL-1-dependent formation of K63-Ub chains, TAK1 activation, or IL-8 production in human cells, because Pellino1 and Pellino2 generate the K63-Ub chains required for signaling in cells expressing E3 ligase-inactive TRAF6 mutants. The IL-1-induced formation of K63-Ub chains and ubiquitylation of IRAK1, IRAK4, and MyD88 was abolished in TRAF6/Pellino1/Pellino2 triple-knockout (KO) cells, but not in TRAF6 KO or Pellino1/2 double-KO cells. The reexpression of E3 ligase-inactive TRAF6 mutants partially restored IL-1 signaling in TRAF6 KO cells, but not in TRAF6/Pellino1/Pellino2 triple-KO cells. Pellino1-generated K63-Ub chains activated the TAK1 complex in vitro with similar efficiently to TRAF6-generated K63-Ub chains. The early phase of TLR signaling and the TLR-dependent secretion of IL-10 (controlled by IRAKs 1 and 2) was only reduced modestly in primary macrophages from knockin mice expressing the E3 ligase-inactive TRAF6[L74H] mutant, but the late-phase production of IL-6, IL-12, and TNFα (controlled only by the pseudokinase IRAK2) was abolished. RANKL-induced signaling in macrophages and the differentiation of bone marrow to osteoclasts was similar in TRAF6[L74H] and wild-type cells, explaining why the bone structure and teeth of the TRAF6[L74H] mice was normal, unlike TRAF6 KO mice. We identify two essential roles of TRAF6 that are independent of its E3 ligase activity.